Structure, Function, Pharmacology, and Therapeutic Potential of the G Protein, Gα/q,11 - Kamato, Danielle; Thach, Lyna; Bernard, Rebekah; Chan, Vincent; Zheng, Wenhua; Kaur, Harveen; Brimble, Margaret; Osman, Narin; Little, Peter J. (Frontiers in Cardiovascular Medicine, 2015)
G protein coupled receptors (GPCRs) are one of the major classes of cell surface receptors and are associated with a group of G proteins consisting of three subunits termed alpha, beta, and gamma. G proteins are classified into four families according to their α subunit; Gαi, Gαs, Gα12/13, and Gαq. There are several downstream pathways of Gαq of which the best known is upon activation via guanosine triphosphate (GTP), Gαq activates phospholipase Cβ, hydrolyzing phosphatidylinositol 4,5-biphosphate into diacylglycerol and inositol triphosphate and activating protein kinase C and increasing calcium efflux from the endoplasmic reticulum. Although G proteins, in particular, the Gαq/11 are central elements in GPCR signaling, their actual roles have not yet been thoroughly investigated. The lack of research of the role on Gαq/11 in cell biology is partially due to the obscure nature of the available pharmacological agents. YM-254890 is the most useful Gαq-selective inhibitor with antiplatelet, antithrombotic, and thrombolytic effects. YM-254890 inhibits Gαq signaling pathways by preventing the exchange of guanosine diphosphate for GTP. UBO-QIC is a structurally similar compound to YM-254890, which can inhibit platelet aggregation and cause vasorelaxation in rats. Many agents are available for the study of signaling downstream of Gαq/11. The role of G proteins could potentially represent a novel therapeutic target. This review will explore the range of pharmacological and molecular tools available for the study of the role of Gαq/11 in GPCR signaling.